Multi‐stress resilience in plants recovering from submergence. Issue 3 (14th November 2022) - Yuan, Li‐Bing; Chen, Mo‐Xian; Wang, Lin‐Na; Sasidharan, Rashmi; Voesenek, Laurentius A. C. J.; Xiao, Shi
Summary: Submergence limits plants' access to oxygen and light, causing massive changes in metabolism; after submergence, plants experience additional stresses, including reoxygenation, dehydration, photoinhibition and accelerated senescence. Plant responses to waterlogging and partial or complete submergence have been well studied, but our understanding of plant responses during post‐submergence recovery remains limited. During post‐submergence recovery, whether a plant can repair the damage caused by submergence and reoxygenation and re‐activate key processes to continue to grow, determines whether the plant survives. Here, we summarize the challenges plants face when recovering from submergence, primarily focusing on studies of Arabidopsis thaliana and rice ( Oryza sativa ). We also highlight recent progress in elucidating the interplay among various regulatory pathways, compare post‐hypoxia reoxygenation between plants and animals and provide new perspectives for future studies.